THE IMPLEMENTATION OF CRIMINAL SANCTIONS ON CHILDREN ADDICTION NARCOTICS IS RELATED TO LEGAL PROTECTION EFFORTS FOR CHILDREN (Study Number 1 / Pid.Sus-Anak / 2019 / PN.Sbg) - FITRIA RISKY FARIE (LP2MTBM MAKARIOZ, 2020)
Narcotics that ensnare minors are sanctioned in accordance with Law No. 35/2009 concerning Narcotics, but in this case minors in accordance with the Criminal Code receive legal protection in accordance with Law No. 11/2012 concerning the System Criminal Protection of Children. Where minors get light sentences to be returned to their parents or get job training in job training for 6 (six) months at the Social Service of North Sumatra Province.The problems contained in this thesis are the first, what are the factors that cause children to commit drug abuse. second, how is the legal protection for children using narcotics according to Law Number 35 of 2014 in conjunction with Law Number 35 of 2009 and third, how is it related to Decision Number 1 / Pid.Sus-Anak / 2019 / PN / Sbg with the Criminal Justice System against Children (SPPA).This study uses normative research called document studies conducted by the author by searching and studying documents or library materials, such as books, papers, scientific journals, magazines, newspapers, and information on the internet.The results of the study revealed that the Criminalization of Children under Law Number 11 Year 2012 concerning the Juvenile Justice System is a basis for imposing sanctions on children who commit criminal acts. Internal factors include the inability of adolescents to make social adjustments or adapt to values ​​and norms that exist in society. The big external factor influencing children with crime is family, in this case the condition of the family environment. The condition of the family environment during the development of children and adolescents has long been considered to have a relationship with the emergence of antisocial behavior and crime committed by adolescents. Judge's consideration in the case of a child caught in a narcotics crime in decision Number 1 / Pid.Sus-Anak / 2019 / PN.Sbg. that the child named Nurul Bintang Fradilla Alias ​​Nurul was charged with Article 127 Paragraph (1) Jo Article 55 Paragraph (1) of Law Number 11 Year 2012 concerning the Criminal Justice System for Children where the child was sentenced to prison for 1 (one year) forever.